1967
DOI: 10.1007/bf03003718
|View full text |Cite
|
Sign up to set email alerts
|

Hyperpyrexia during anaesthesia in a second member of a family, with associated coagulation defect due to increased intravascular coagulation

Abstract: HYPERPYREXIA following anaesthesia, and associated with an abnormal reaction to succinylcholine (Anectine| though rare, has been the subject of a number of reports recently. 1-4 The following case is reported to alert anaesthetists to a possible familial tendency to hyperthermia, and the simultaneous occurrence of an alteration in the coagulating mechanisms of the blood. A married woman of French-Canadian descent, aged 44, was anaesthetized on December 14, 1966, for excision biopsy of a mass in the left breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1968
1968
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Pari passu a gross metabolic and respiratory acidosis was evident. Whereas the limbs of the normal anaesthetized pig are relaxed during anaesthesia-even light anaesthesia-the limbs of the hyperpyrexial pigs were stiffly extended, the muscles in extreme spasm in a way similar to that described by Hall et al (1966) in their pigs and by the Canadian workers (Cullen, 1966 ;Davies and Graves, 1966;Hogg and Renwick, 1966;Lavoie, 1966;Relton et al, 1966;Thut and Davenport, 1966;Purkis et al, 1967) in the hyperpyrexial humans following the suxamethonium they postulated as being responsible for this condition. We did not observe any marked change in pulmonary compliance.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Pari passu a gross metabolic and respiratory acidosis was evident. Whereas the limbs of the normal anaesthetized pig are relaxed during anaesthesia-even light anaesthesia-the limbs of the hyperpyrexial pigs were stiffly extended, the muscles in extreme spasm in a way similar to that described by Hall et al (1966) in their pigs and by the Canadian workers (Cullen, 1966 ;Davies and Graves, 1966;Hogg and Renwick, 1966;Lavoie, 1966;Relton et al, 1966;Thut and Davenport, 1966;Purkis et al, 1967) in the hyperpyrexial humans following the suxamethonium they postulated as being responsible for this condition. We did not observe any marked change in pulmonary compliance.…”
Section: Resultssupporting
confidence: 59%
“…The baffling and frightening complication of malignant hyperpyrexia occurring during anaesthesia has been described in humans by many authors (Cullen, 1966 ;Davies and Graves, 1966;Hogg, and Renwick, 1966;Lavoie, 1966;Relton et al., 1966;Thut and Davenport, 1966;Purkis et al, 1967) and in anaesthetized pigs by Hall et al (1966). Most of these workers attribute this unpredictable, lethal, and puzzling reaction to suxamethonium, genetically determined.…”
Section: Resultsmentioning
confidence: 97%
“…A number of such occurrences have been published, mainly in Canada (Saidman et al, 1964;Cullen, 1966;Davies and Graves, 1966;Hogg and Renwick, 1966; Lavoie, 1966;Relton et al, 1966 ;Thut and Davenport, 1966;Purkis et al, 1967;Stephen, 1967), but we know of only one other comparable case so far recorded in the British Isles (Brown, 1954).…”
mentioning
confidence: 99%
“…med.J., 1968, 3, 594-595 S ummary: Work in pigs has shown that malignant hyperpyrexia during anaesthesia may occur without suxamethonium having been given. A virtually constant feature in reported cases and in our own observations is that all subjects developing hyperpyrexia had received nitrous oxide and halothane.The baffling and frightening complication of malignant hyperpyrexia occurring during anaesthesia has been described in humans by many authors (Cullen, 1966 ;Davies and Graves, 1966;Hogg, and Renwick, 1966; Lavoie, 1966;Relton et al., 1966;Thut and Davenport, 1966;Purkis et al, 1967) stiffly extended, the muscles in extreme spasm in a way similar to that described by Hall et al (1966) in their pigs and by the Canadian workers (Cullen, 1966 ;Davies and Graves, 1966;Hogg and Renwick, 1966; Lavoie, 1966;Relton et al, 1966;Thut and Davenport, 1966;Purkis et al, 1967) in the hyperpyrexial humans following the suxamethonium they postulated as being responsible for this condition. We did not observe any marked change in pulmonary compliance.…”
mentioning
confidence: 99%